Approaches to nutritional management in patients with COVID-19: an integrative review (Research, Society and Development, 2021)
The aim of this study was to conduct a survey in the scientific literature of possible nutritional therapies addressed in patients with covid-19. It is an integrative review, in which searches were performed in the PubMed, Scopus and Web of Science databases, including only scientific articles published in the years 2020 to 2021. For the search key, the following descriptors were considered: “Nutrition Therapy ”; “Coronavirus Infections” and synonyms in English, where 1,152 studies were found, of which 8 were included. The articles analyzed presented different nutritional behaviors; as a result, early nutritional support with slow progression was observed as an efficient alternative, as well as enteral nutrition therapy starting within the first 24h or 48h of admission to the ICU. Nevertheless, nutritional risk is a relevant factor in these patients, in which malnutrition is present in most cases, however, maintaining an adequate nutritional status is a priority for their survival. Thus, adequate nutritional management is essential for patients infected with covid-19, in which adequate support with enteral nutrition and supplementation with omega-3 are favorable for the recovery and survival of these patients, however, more studies are needed to this last statement.